1995
DOI: 10.1136/bmj.311.7015.1255
|View full text |Cite
|
Sign up to set email alerts
|

Changes in population cholesterol concentrations and other cardiovascular risk factor levels after five years of the non-communicable disease intervention programme in Mauritius

Abstract: Lifestyle intervention projects can be implemented and have positive effects in developing countries. A pronounced improvement in the population lipid profile in Mauritius was probably related to a change in the saturated fat content of a widely used cooking oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
2
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(151 citation statements)
references
References 25 publications
11
136
2
2
Order By: Relevance
“…31,32 Such a population-wide intervention programme has been successfully implemented in Mauritius. 33 People of African origin often display more sodium sensitivity than non-Africans. Therefore, a modest reduction in sodium intake could considerably reduce BP and cardiovascular morbidity.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…31,32 Such a population-wide intervention programme has been successfully implemented in Mauritius. 33 People of African origin often display more sodium sensitivity than non-Africans. Therefore, a modest reduction in sodium intake could considerably reduce BP and cardiovascular morbidity.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…The success of such comprehensive programmes has been demonstrated in the varied settings of developed, as well as developing, countries 31,32 . In addition, populations at high risk need strategies and services for early detection and effective control of risk.…”
Section: Public Health Responsesmentioning
confidence: 99%
“…Given the projected epidemic of diabetes in China [5], such a potentially cost-effective intervention is of great importance. We have also recently shown that a similar community-based lifestyle approach in Mauritius could reduce some of the key risk factors for Type II diabetes and CVD such as eating behaviour, sedentariness, serum lipids and cigarette smoking [149,150].…”
Section: Primary Prevention Of Type II Diabetesmentioning
confidence: 99%